Paścimanā deśonī keḷavaṇī Amerikā, Raśiyā, Iṅglāṇḍa, Phrānsa, Jarmanī, ane Iṭālīnī keḷavaṇī paddhationī Hindī dr̥shṭie māhitī ane samālocanā - Khaira, Gajānana Śrīpata, 1898- (SAMP early 20th-century Indian books project, 1938)
Translation of a Marathi work on Western education.